Adaptasi Konsep Imbal Jasa Lingkungan Sebagai Persyaratan Pendaftaran Paten Yang Menggunakan Bahan Sumber Daya Genetik Di Indonesia - Andini, Vika (UI Scholars Hub, 2015)
Natural resources exploitation not only have an effect to the balance of environment ecosystem but also to the indigenous people as a caretaker for the genetic resources. The indigenous people are the most entitled ones to gain the commercial benefit from the use of the genetic resources.The protection and benefit sharing for the use of genetic resources need to be reaffirmed in the existing national law instrument. The provision about the protection and benefit sharing in the use of genetic resources can not only regulated in environment law instrument, but should regulated in intellectual property right law instrument as well. Patent law is the most related closely in the use of genetic resources, considered as the most concordant to regulate the protection of genetic resources and the benefit sharing as well.